Decadent Genealogies The Rhetoric of Sickness from Baudelaire to D'Annunzio - Spackman, Barbara (Cornell University Press, 2018)
Barbara Spackman here examines the ways in which decadent writers adopted the language of physiological illness and alteration as a figure for psychic otherness. By means of an ideological and rhetorical analysis of scientific as well as literary texts, she shows how the rhetoric of sickness provided the male decadent writer with an alibi for the occupation and appropriation of the female body.Barbara Spackman here examines the ways in which decadent writers adopted the language of physiological illness and alteration as a figure for psychic otherness. By means of an ideological and rhetorical analysis of scientific as well as literary texts, she shows how the rhetoric of sickness provided the male decadent writer with an alibi for the occupation and appropriation of the female body.